THE CIBMTR HEMATOPOIETIC CELL TRANSPLANT RECIPIENT TRANSFER TOOL FOR FOLLOW UP MAINTENANCE: ADHERENCE ASSESSMENT OF 24 BRAZILIAN CENTERS AND ONE URUGUAYAN - da Costa-Junior, Luiz Carlos; da Silva, Cinthya Corrêa; João Simione, Anderson; Monique Ammi; Izu, Marina; Moreira da Silva Sabaini, Paula; Di Chiara Salgado, Jessica; Vaz de Macedo, Antônio; Alves das Neves, Heliz Regina; da Silva Santos Geraldo, Bruna Letícia; Ferreira Costa, Flavia; Viana, Valeria; et al. (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2025)
Introduction: Hematopoietic Cell Transplantation (HCT) remains a curative treatment for several malignant and non-malignant hematologic diseases. Despite significant advances in the field, maintaining long-term clinical follow-up continues to be a major challenge. To enhance continuity of care, the Center for International Blood and Marrow Transplant Research (CIBMTR) developed the patient transfer tool within FormsNet3, allowing the transfer of CRID identifiers between affiliated centers. However, little is known about the extent of adherence to this tool among South American centers. Objective: To evaluate the adherence of South American centers to the CIBMTR patient transfer tool, aiming to identify gaps and opportunities to improve data completeness and patient monitoring after HCT. Methods: An electronic questionnaire was distributed to South American centers actively participating in the CIBMTR, with at least 12 consecutive months of data reporting. The survey collected information on institutional characteristics, transplant volume, and experience with the CRID transfer tool. Data were analyzed using descriptive statistics and visualized through the Power BI platform. Results: Twenty-five centers participated in the study, representing 49% of active South American centers in the CIBMTR, of which 96% were Brazilian. Most centers were located in the Southeast region (70.8%) and included a variety of institutional types: private (44%), public (36%), and mixed (20%) hospitals. Regarding experience with the transfer tool, 60% of centers reported transferring patients, accounting for 67 movements (32 sendings and 35 receivings), predominantly involving adult patients undergoing allogeneic transplants. An asymmetric transfer pattern was observed: public centers primarily received transferred patients, whereas private centers were the main origin centers. Conclusion: Although the CIBMTR CRID-patient transfer tool represents a significant advancement in promoting long-term follow-up, its adoption remains limited among South American centers. Low adherence could jeopardize continuity of care and data completeness, ultimately impairing surveillance of late complications and hindering the development of effective prevention strategies.